Partnership or Marriage of Convenience? - Sentes, Ray (Relations industrielles / Industrial Relations, 1976)
This article reviews "Partnership or Marriage of Convenience? (A critical examination of by contemporary labour-relations in West Germany with suggestions for improving the Canadian Labour-management relationships based on the West German experience)" by Charles Connaghan.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z